Frequency of wet and dry spells at five stations in Rajasthan - GUPTA, B. R. D. (MAUSAM, 1966)
Frequencies of wet and dry spells at five stations in Rajasthan (Bikaner, Jodhpur, Ajmer, Jaipur and Udaipur) for the south-west monsoon period are studied. The study is based on the daily rainfall data of these stations from 1891 to 1919. It is seen that frequencies of rain spells of less tb.a.n5 days are common and those greater than 10 days are extremely rare. Frequencies of dry spells of less than 5 days are common for all the five stations. Frequencies of dry spells greater th-an 15 days are also common at Bikaner, Jodhpur and Ajmer but are less frequent (20 per cent of the total days) at Jaipur and Udaipur. Intercorrelation coefficients among the stations for all dry spells of two days and more are found to be significant for Bikaner-Jodhpur, Bikaner-Ajmer and Jodhpur-Ajmer and Jaipur-Udaipur.